Different responses after intracerebral hemorrhage between young and early middle-aged mice. (14th September 2020) - Kinoshita, Keita; Ohtomo, Ryo; Takase, Hajime; Hamanaka, Gen; Chung, Kelly K.; Lok, Josephine; Katsuki, Hiroshi; Arai, Ken
Highlights: 8-month old mice were compared with 2-month old mice after intracerebral hemorrhage. There was no significant difference in lesion volume at day 8 between the two groups. 8-month old mice showed delayed recovery along with reduced astrocytic activation. Abstract: Although aging is a major risk factor for intracerebral hemorrhage (ICH), there are very few studies comparing ICH pathology between young and early middle-aged mice. In this study, 8-month old mice (early middle-aged mice) were compared against 2-month old mice (young mice) in neurological and histological changes after ICH induction, such as body weight, lesion volume, astrocytic responses, and motor and cognitive functions. At day 8 after ICH, there was no significant difference in lesion volume between the two groups, and both groups did not exhibit significant cognitive decline, as assessed by spontaneous alternative Y-maze test. On the other hand, 8-month old mice showed delayed recovery from body weight loss, along with reduced astrocytic activation. Interestingly, in the two motor function tests (beam-walking test and corner turn test), 8-month old mice exhibited lower scores only in the beam-walking test, suggesting a partial disturbance in motor recovery after ICH. These results suggest that age-related differences in ICH pathology may already start to appear in early middle-aged brains.